PEGARUH RASIO-RASIO CAEL TERHADAP TINGKAT KESEHATAN LPD DI KECAMATAN MENGWI KABUPATEN BADUNG. - Ketut Sudarmini; Ni Putu Rediatnigiri; Ni Made Rustini (Lembaga Penelitian, Universitas Warmadewa, 2017)
Institute the countryside credit (LPD) representing body of effort property of custom countryside (BUMDA) running its function as financial institution can give the credit to support the fluency of effort good bussines. Without supported by capital which enough hence fluency from activity of effort bussines can be annoyed, this matter non representing the intention of a business activity. Therefore capital own the very important role to realize the target bussiness. So the LPD can run its function as institute which can give the loan / credit to all its client, hence of course the LPD have to remain to keep in good health its so that healthy always by paying attention to ratio which can influence the health storey;level. For that hence this research aim to : (1) to analysing ratio CAEL simultaniously to storey;level of health LPD in Mengwi badung Regency. (2) knowing the level of influence of each ratio CAEL to storey;level of health LPD in Mengwi Badung Regency, (3) knowing ratio CAEL which dominant influence the storey;level of health LPD in Mengwi BadungRegency. This Object Research is ratio CAEL at 38 LPD of exist in three subdistrict in Mengwi Badung Regency . Intake sample conducted in census. Data used in this research is secondary data in the form of financial statement and ratio CAEL for the period of year 2015. Analysis method used is analysis : test the classic assumption, regression with the program SPSS 16. This Research result indicate that : (1) there is influence significantly by simultan among capital ratio, asset, rentability, and likuidity or CAEL to storey;level of health LPD in Mengwi Badung Regency, (2) level of influence of each capital ratio, asset, rentability, and likuidity to health storey;level institute the credit people shall be as follows : (a) ratio CAR to storey;level of health LPD equal to 25,90 %, (b) ratio KAP to storey;level of health LPD equal to 39,00 %, (c) ratio CPRR to storey;level of health LPD equal to 23,20 %, (d) ROA to storey;level of health LPD equal to 80,50 %, (e) ratio BOPO to storey;level of health LPD equal to 11 %, (f) ratio likuidity to storey;level of health LPD equal to 60,50 %, (g) ratio LDR to storey;level of health LPD equal to 18,80 % and (3) from seven ratio analysed in the reality Return on Assetsy ratio owning influence most dominant influence the storey;level of health LPD in Mengwi Badung Regency. This Research recommend to organizer LPD to conduct the credit construction in order not to there is no problem credit which is a period of so that LPD always healthy in a condition. Key Word: CAEL, Level of Health, LPD